Validation and adaptation of the Indonesian version of thyroid cancer quality of life questionnaire - Pramono, Laurentius Aswin; Shatri, Hamzah; Subekti, Imam; Prihartono, Nurhayati Adnan; Hatma, Ratna Djuwita; Kurniawidjaja, Meily; Prasetyo, Sabarinah; Kurniawan, Felicia (Medical Journal of Indonesia, 2025)
BACKGROUND The rising incidence of thyroid cancer in Indonesia has become a public health concern. This study was aimed to evaluate the validity of the thyroid cancer-quality of life-Indonesian version (ThyCa-QoL-ID). METHODS This cross-sectional study involved translating the original ThyCa-QoL questionnaire from English to Indonesian (T1), which was then back-translated into English (T2). The T2 questionnaire was compared with the original ThyCa-QoL questionnaire to refine T1, resulting in T3. The T3 questionnaire underwent cognitive and transcultural validation through individual assessment and focus group discussions with 10 doctors and 10 nurses at Cipto Mangunkusumo Hospital and St. Carolus Hospital, and 5 patients with thyroid cancer from St. Carolus Hospital. This process ensured cultural, language, and literacy adaptation processes for patients across different age groups. RESULTS The ThyCa-QoL questionnaire demonstrated validity, with all questions showing correlation calculation (r) above the r table. Test-retest reliability was measured by calculating the intraclass correlation coefficient for each question on the ThyCa-QoL questionnaire. The reliability test can be seen in the value of Cronbach’s alpha (0.915), exceeding the standard Cronbach’s alpha value standard (0.6). CONCLUSIONS The ThyCa-QoL-ID was confirmed as a valid and reliable tool for assessing the QoL of patients with thyroid cancer in Indonesia.